TO EVALUATION OF TREATMENT OUTCOMES OF SEVERE STROKE PATIENTS TREATED WITH TARGETED TEMPERATURE MANAGEMENT (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of severe stroke patients treated with targeted temperature management.Subjects and methods: Prospective and retrospective descriptive study on 12 severe stroke patients at the Intensive Care Unit - Nghe An Friendship General Hospital from January 2023 to June 2025.Results: The mean age was 50.16 ± 11.92 years. Intracerebral hemorrhage with intraventricular extension accounted for 75.0% of cases. Combined decompressive hematoma evacuation and ventricular drainage was performed in 66.7% of patients. Mean Glasgow score tended to improve from 6.6 at initiation of temperature control to 8.1 after rewarming and 24-hour temperature maintenance. All patients survived to hospital discharge; 8/12 patients (66.7%) were alive at 30 days, and 5/12 patients (41.7%) were alive at 6 months. All survivors at 6 months had CPC scores from 1 to 3.Conclusion: The targeted temperature management technique using surface cooling device initially shows effectiveness in treating severe stroke patients.
Keywords: Targeted temperature management; Stroke; Cerebral Performance Category